THE IMPACT OF ENTREPRENEUSHIP EDUCATION, INTERNAL LOCUS OF CONTROL, PRESENTATION NEED, CREATIVITY, GENDER AND FAMILY TOWARDS ENTREPRENEURSHIP INTENTION ON STUDENTS IN POLINEMA ACCOUNTANCY FACULTY - Andi Asdani; Anik Kusmintarti (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2014)
The purpose of this study is to analyze how the influence of Entrepreneurship Education, Internal Locus of Control, the Necessity of Achievement, Creativity, Gender and Family Against intention Entrepreneurship. Samples are accounting majors followed the entrepreneurship education by 100 respondents with purposive sampling technique. The analytical tool used is descriptive analysis and inferential analysis is linear regression with significant test F and t. Results of the analysis states that (1) jointly entrepreneurship education, inernal locus of control, need for achievement, creativity, gender, the family has a significant influence on intense entrepreneurship, (2) more often followed the entrepreneurship education for students entrepreneurial intentions Polytechnic Malang higher, (3) The higher the ability to control internal locus of control intention of entrepreneurship for students Polytechnic of Malang higher, (4) higher need for achievement, the intentions of entrepreneurship for students of the higher Polytechnic of Malang, (5) Higher creativity, entrepreneurial intentions for students of the higher Polytechnic of Malang, (6) Men have influence entrepreneurial intentions for students Polytechnic of Malang higher than women, (7) The higher the entrepreneurial intention MKA family support for students Polytechnic of Malang will be higher.